Jayaprakash Narayan selected works - Narayan, Jayaprakash; Prasad, Bimal (Ed.) (New Delhi Manohar, 2000)
This Volume has been planned with a view to presenting as full a picture as possible of the evolution of J.P's politics and thought through his writings, speeches and letters. As he was in many ways a mirror of his times, this volume provides an idea of t
Keywords: Narayan, Jayaprakash-Collections; Anthologies; Literature-Collections